DSM-5 schizoaffective disorder: will clinical utility be enhanced? (2015)
Recently, the latest edition of the Diagnostic and Statistical Manual (DSM), the DSM-5, was published following extensive scrutiny and elaborate revision of the DSM-IV. According to the American Psychiatric Association (APA), the main concerns in modifying DSM-IV included opti mizing clinical utility, upholding continuity with previous editions, and that recommendations should be directed by research evidence [1]. Therefore, the result expected was to be a text that is more useful for medical practitioners, patients and policy makers, and which should reveal not only scientific advances in our understanding of the causes and consequences of psychiatric disorders, but also com mon usage.